Digital Literacy and Self-Efficacy Development Strategies for Technostress Coping Among Older Lecturers in Higher Education Institutions - Aditya Andika (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The massive and rapid digitalization of higher education institutions, which was further accelerated by the COVID-19 pandemic, has increased the level of technostress experienced by university lecturers. This condition is particularly evident among older lecturers who are required to adapt to various new digital technologies in their teaching and academic activities. This paper aims to explore strategies for the development of digital literacy and self-efficacy as efforts to cope with technostress, specifically by considering the needs, strengths, and limitations of older lecturers in higher education institutions. This study is based on a literature review on technostress and adult learning theory. On the basis of this review, a comprehensive framework focusing on the development of digital literacy and technological self-efficacy is proposed by applying andragogical principles. It is expected that the findings of this study can provide evidence-based strategies to assist older lecturers in managing technostress while maintaining teaching quality and personal well-being.